STUDI TENTANG PENERAPAN ASAS VERHANDLUNGS MAXIME DALAM PEMERIKSAAN PERKARA PERDATA - Sigit Dwi Nugroho; Ismawati Septiningsih; Itok Dwi Kurniawan (Universitas Suryakancana, 2023)
In civil procedural law there are principles that must be met, one of which is fulfilling the legal principle, the Verhandlungs Maxime principle has the understanding that the scope or main area of the dispute submitted to the judge for examination is basically determined by the parties to the case and not by the judge. In practice, if the Verhandlungs Maxime principle is applied absolutely in trying cases, it can cause the principle of justice or the principle of expediency not to be fulfilled. There is a need for research related to the application of the Verhandlungs Maxime principle in the examination of civil cases to determine the scope of this principle. The research method used in the preparation of this study is a normative juridical method. Judges in deciding a case must pay attention to the Verhandlungs Maxime principle so that the resulting decision is not considered Ultra Petita, but the judge has the freedom to decide outside the subject of the dispute submitted by the parties based on the theory of legal objectives by Gustav Radbruch, Law Number 48 of 2009 concerning Power Judiciary, and Supreme Court Jurisprudence. An understanding is needed regarding the arrangement and application of the Verhandlungs Maxime principle in the Civil Procedure Code, other regulations related to the verhandlungs maxime principle, and the development of the application of the principle so that there is a uniform understanding of the verhandlungs maxime principle.Â Keywords: Civil Case, Legal Principles, Verhandlungs Maxime.